You should remember that `sec x = 1/cos x` , hence `sec^4 x = 1/(cos^4 x)` such that:

`int sec^4 x dx= int 1/(cos^4 x) dx`

You should use the fundamental formula of trigonometry such that:

`sin^2 x + cos^2 x = 1`

Substituting `sin^2 x + cos^2 x` for 1 yields:

`int (sin^2 x + cos^2 x)/(cos^4 x) dx`

Using the property of linearity of integrals yields:

`int (sin^2 x + cos^2 x)/(cos^4 x) dx = int (sin^2 x)/(cos^4 x) dx ` `+ int (cos^2 x)/(cos^4 x) dx `

`int (sin^2 x + cos^2 x)/(cos^4 x) dx = int tan^2 x*sec^2 x dx + int sec^2 x dx`

You need to solve the integral `int tan^2 x*sec^2 x dx` using substitution `tan x = t => sec^2 x dx = dt` such that:

`int tan^2 x*sec^2 x dx = int t^2 dt = t^3/3 + c`

Substituting back `tan x ` for t yields:

`int tan^2 x*sec^2 x dx = (tan^3 x)/3 + c`

`int (sin^2 x + cos^2 x)/(cos^4 x) dx = (tan^3 x)/3 + tan x + c`

**Hence, evaluating the given integral yields `int (sin^2 x + cos^2 x)/(cos^4 x) dx = (tan^3 x)/3 + tan x + c.` **